Effect of CNTs on Mechanical and Abrasion Properties of NBR. Issue 1 (September 2020) - Yuan, Song; Wen, Jun; Zhang, Qiong
Abstract: Mechanical properties, abrasion properties and morphology of CNTs/NBR were studied in this paper. The addition of carbon nanotubes can effectively improve the aging and wear resistance of rubber composites. SEM demonstrated that agglomeration phenomenon occurs when the content reaches 4phr.